Doctor Adam Talib's Public Relations Strategy in Improving the Quality of Patient Service - Putri, Anggun Kartika; Alzboon, Mowafaq Salem (Yayasan Sinergi Kawula Muda, 2023)
As time goes by, hospitals are now facing an era of global competition in various medical fields. The rapid development of science and technology in the medical field has created competition between hospitals. This increasingly fierce competition requires hospitals to provide the best service. This study aims to determine the public relations strategy in improving the quality of service at the Adam Talib Hospital. This research is qualitative. The data obtained using interview, observation, and documentation techniques. The results of this research are the strategies applied by public relations, namely: 1. One Rate Service, 2. Service Without Down Payment, 3. Employee Training, 4. Evaluation Meeting, 5. Customer Satisfaction Survey, 6. 24 Hour Laboratory Service, 7. Customer 24 Hours Service. The obstacles faced were: 1. Patients went home at their own request, 2. Covid 19, 3. High competition, 4. Negative testimonials, 5. Patients did not understand medical language. Then the efforts made are: 1. Collaborating with Kitabisa, 2. Promoting on Social Media, 3. Implementing Health Protocols, 4. Using language that is easy for patients to understand. There is a strategy that is applied in addition to creating a good image of the Adam Talib Hospital but also to increase the number of new customers, increase patient trust, increase relationships with other parties, and increase customer loyalty.